Teaching Strategies for Learners with Special Needs in Mainstream Classes - Ritaga, Janice (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the teaching strategies employed for learners with special needs in mainstream classes in selected public secondary schools in the Binangonan District during the School Year 2025–2026. Utilizing a descriptive survey research design, the study involved 96 teachers from Don Jose M. Ynares Sr. Memorial National High School, Guronasyon Foundation Incorporated National High School, and Mahabang Parang National High School. A researcher-made questionnaire-checklist was used to gather data on the extent of teaching strategies applied, specifically in terms of differentiated instruction, individualized instruction, multisensory instruction, and technology-based instruction, as well as the challenges encountered by teachers.Findings revealed that most respondents were middle-aged, female, and married, with diverse educational backgrounds and teaching experiences. The majority specialized in Araling Panlipunan and Technology and Livelihood Education (TLE), and frequently attended school-level trainings. Teachers often employed varied teaching strategies to support learners with special needs, with differentiated and individualized instruction being the most prominent. Statistical analysis showed that age, length of service, and area of specialization significantly influenced the use of teaching strategies, while sex, civil status, educational attainment, position title, and in-service training did not.Moreover, teachers commonly faced challenges such as lack of learning resources, difficulty in managing student behavior, stressful teaching conditions, and overcrowded classrooms. The study concluded that certain teacher-related factors influence the effective use of inclusive teaching strategies. It is recommended that learners with special needs be provided with diverse instructional approaches, and that educational authorities allocate sufficient resources to support inclusive education. The implementation of the proposed action plan and further research involving additional variables are also encouraged.
Keywords: special needs education, inclusive education, teaching strategies, differentiated instruction, mainstream classes, teacher factors